The metaconglomerates of the eastern Lanterman Range (northern Victoria Land, Antarctica): new constraints for their interpretation - Capponi, G.; Crispini, L.; Meccheri, M. (Antarctic Science, 1999)
Highly deformed metaconglomerates, mafic to felsic in composition, characterize the eastern Lanterman Range (northern Victoria Land, Antarctica). In the literature the mafic and felsic metaconglomerates are known as Husky Conglomerate and Lanterman Conglomerate respectively. They occurin a 25 km long strip along the Lanterman Fault, which is a major tectonic boundary between the Wilson and the Bowers terranes. New field observations show that there is a gradual transition from mafic to felsic metaconglomerates: this supports a stratigraphical continuum from Husky to Lanterman Conglomerate, and indicates that they belong to the same sedimentary succession. Structural analysis indicates that Husky and Lanterman conglomerates suffered the same structural evolution. From all these evidences, there is no reason to distinguish two types of metaconglomerates, apart from the diversity in the lithological features. However the two terms "Husky Conglomerate" and "Lanterman Conglomerate" can be still used to refer to the mafic and felsic facies of the same sedimentary succession. On the basis of their lithology the Husky Conglomerate can be derived from the Glasgow volcanic are, whereas the felsic clasts of the Lanterman Conglomerate may be derived from a continental basement below the Glasgow are or from a continental block bounding the Bowers trough.